Differential efficacy of salicylic acid-induced resistance against bacterial blight caused by Xanthomonas oryzae pv. oryzae in rice genotypes - Meesa Natchanon; Ratanasut Kumrop; Laothaworn Walailak; Rungrat Tepsuda; Buddhachat Kittisak; Sujipuli Kawee; Inthima Phithak (Open Agriculture)
Source: Created by the authors.